Leveraging Popular Destinations to Enhance Web Search Interaction - White, Ryen W.; Bilenko, Misha; Cucerzan, Silviu (ACM Transactions on the Web, 2008)
This article presents a novel Web search interaction feature that for a given query provides links to Web sites frequently visited by other users with similar information needs. These popular destinations complement traditional search results, allowing direct navigation to authoritative resources for the query topic. Destinations are identified using the history of search and browsing behavior of many users over an extended time period, and their collective behavior provides a basis for computing source authority. They are drawn from the end of users’ post-query browse trails, where users may cease searching once they find relevant information. We describe a user study that compared the suggestion of destinations with the previously proposed suggestion of related queries, as well as with traditional, unaided Web search. Results show that search enhanced by query suggestions outperforms other systems, in terms of subject perceptions and search effectiveness, for fact-finding search tasks. However, search enhanced by destination suggestions performs best for exploratory tasks, with best performance obtained from mining past user behavior at query-level granularity. We discuss the implications of these and other findings from our study for the design of search systems that utilize user behavior, in particular user browse trails and popular destinations.